A high-adhesion waterproof coating, preparation method and application on profiles

By using modified reduced graphene oxide and binary copolymer as modifiers, a high adhesion waterproof coating was prepared, which solved the problem of insufficient adhesion of existing waterproof coatings and significantly improved waterproof performance and wear resistance.

CN118895084BActive Publication Date: 2025-02-07SHANGHAI JIREN COMPOSITE MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411399123.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-07
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing waterproof aluminum alloy material has insufficient adhesion, which causes the coating to fall off and affects the waterproof effect.

Method used

Modified reduced graphene oxide and binary copolymer are used as modifiers to prepare high adhesion waterproof coatings by mixing and curing with polyurethane emulsion. The coating is grafted to reduce graphene oxide by intermediate product A, and multiple branch chains are introduced to improve dispersion and cross-linking density, and enhance the mechanical properties, wear resistance and waterproof properties of the coating.

Benefits of technology

It significantly improves the adhesion between the coating and aluminum alloy profile, improves waterproof performance and wear resistance, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895084B_ABST
    Figure CN118895084B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of coating preparation, and discloses a high-adhesion waterproof coating, a preparation method and an application on a profile. The preparation method of the high-adhesion waterproof coating comprises the following steps: 3,4,5-trihydroxybenzaldehyde reacts with 4,4'-dithiodiphenylamine to obtain an intermediate product A; the reduced graphene oxide is modified with the intermediate product A to obtain a modified reduced graphene oxide; citric acid is used as a cross-linking agent, 3-butene-1-ol and 3-perfluorohexyl propanol react to obtain an intermediate product B; intermediate product B and glycidyl methacrylate are copolymerized to obtain a binary copolymer; using the binary copolymer and the modified reduced graphene oxide as a modifier, a modified polyurethane is prepared; the modified polyurethane, a hybrid material and other components are mixed to obtain a high-adhesion waterproof coating. The coating of the present invention has excellent waterproof performance and wear resistance, high adhesion with aluminum alloy profiles, and good self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to a high-adhesion waterproof coating, a preparation method and application on profiles. Background Art

[0002] At present, the widely used door and window profile products in China include aluminum alloy (market share is 40%), plastic (PVC) (accounting for 35%) and other materials. Aluminum alloy door and window profiles have the advantages of light weight, high strength, sealing, good sound insulation performance, and beautiful appearance. However, as the area of ​​door and window monomers becomes larger and more wall-like, the leakage of aluminum alloy doors and windows becomes more and more serious. The leakage problem has always been the main factor affecting the use effect and life of aluminum alloy doors and windows in actual engineering applications. The waterproof effect of the waterproof coating on the surface of aluminum alloy will directly affect the leakage. In order to solve the waterproof problem of aluminum alloy, Chinese patent application CN110499075A provides a waterproof aluminum alloy material and its application, including a waterproof coating, which is obtained by applying the waterproof coating on the aluminum alloy body and curing at room temperature for 7 days; the waterproof coating includes an organic solvent, rubber powder and an additive, and the rubber powder and the additive are dispersed in the organic solvent; the waterproof coating forms a waterproof layer on the aluminum alloy body to obtain a waterproof aluminum alloy material. However, the adhesion between the waterproof aluminum alloy material and the waterproof coating is insufficient, which may cause the coating to fall off, thereby affecting the waterproof effect. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a high-adhesion waterproof coating, comprising the following steps:

[0004] Step (1), 3,4,5-trihydroxybenzaldehyde reacts with 4,4'-dithiodiphenylamine to obtain an intermediate product A;

[0005] Step (2), modifying the reduced graphene oxide with the intermediate product A to obtain modified reduced graphene oxide;

[0006] Step (3), using citric acid as a crosslinking agent, reacting 3-butene-1-ol with 3-perfluorohexylpropanol to obtain an intermediate product B; copolymerizing the intermediate product B with glycidyl methacrylate to obtain a binary copolymer;

[0007] Using binary copolymer and modified reduced graphene oxide as modifiers, modified polyurethane is prepared;

[0008] Step (4), mixing the modified polyurethane, the hybrid material, deionized water, BYK-024 defoamer, and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and curing to obtain a high-adhesion waterproof coating.

[0009] Wherein, the preparation method of the hybrid material comprises the following steps:

[0010] Step S1, in-situ growing nano-silicon dioxide on the surface of nano-silicon carbide to obtain composite nanoparticles;

[0011] Step S2: modifying the composite nanoparticles with perfluorooctylethyltrimethoxysilane to obtain a hybrid material.

[0012] Preferably, in step (1), the method for preparing the intermediate product A comprises the following steps:

[0013] Add 3,4,5-trihydroxybenzaldehyde to ethanol, stir until dissolved, then add 4,4'-dithiodiphenylamine, reflux at 70-90°C for 10-15h, evaporate to remove the solvent to obtain a primary product, add the primary product to ethyl acetate for washing, stir for 20-40min, centrifuge, repeat the above washing and centrifugation operation 2-4 times, and dry to obtain an intermediate product A; wherein the mass ratio of 3,4,5-trihydroxybenzaldehyde, 4,4'-dithiodiphenylamine, ethanol, and ethyl acetate is (15.4-30.8):(10-20):(50-100):(55-110);

[0014] In the above process, the aldehyde group of 3,4,5-trihydroxybenzaldehyde reacts with the amino group of 4,4'-disulfide diphenylamine to obtain an intermediate product A containing multiple disulfide bonds, imine bonds, phenolic hydroxyl groups, and benzene rings.

[0015] Preferably, in step (2), the method for preparing modified reduced graphene oxide comprises the following steps:

[0016] The reduced graphene oxide is dispersed in N,N-dimethylformamide, and ultrasonically treated for 1-1.5 hours, and then hexamethylene diisocyanate isocyanurate trimer is added, and the reaction is carried out at 70-90°C for 20-30 hours in a nitrogen atmosphere, and then the intermediate product A is added, and the temperature is kept constant, and the reaction is continued for 2-4 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified reduced graphene oxide; wherein the mass ratio of reduced graphene oxide, N,N-dimethylformamide, hexamethylene diisocyanate isocyanurate trimer, and intermediate product A is (1-2): (400-800): (10-18): (10.5-18.8);

[0017] In the above process, the hexamethylene diisocyanate isocyanurate trimer plays the role of a connecting intermediate. An isocyanate group in the hexamethylene diisocyanate isocyanurate trimer first reacts with the hydroxyl group on the surface of the reduced graphene oxide to introduce an isocyanate group on the reduced graphene oxide, and then reacts with the phenolic hydroxyl group in the intermediate product A to graft the intermediate product A on the reduced graphene oxide, thereby introducing multiple side chains on the reduced graphene oxide.

[0018] Preferably, in step (3), the method for preparing the binary copolymer comprises the following steps:

[0019] 3-Butene-1-ol and 3-perfluorohexylpropanol are added to dimethyl sulfoxide, and then citric acid and sodium hypophosphite are added, heated to 70-90°C, and stirred at a speed of 200-400r / min for 1.5-2.5h. After the reaction is completed, the solvent is removed by reduced pressure distillation at 55-65°C, and then dialyzed through a dialysis bag with a molecular weight cutoff of 200D to obtain an intermediate product B; wherein the mass ratio of 3-butene-1-ol, 3-perfluorohexylpropanol, dimethyl sulfoxide, citric acid, and sodium hypophosphite is (1-2):(3.8-7.6):(100-300):(2.5-5):(0.06-0.1);

[0020] The intermediate product B is added to n-propanol, ultrasonically mixed for 20-40 minutes, and then glycidyl methacrylate and azobisisobutyronitrile are added, heated to 50-70°C in a nitrogen atmosphere, stirred at a speed of 200-400 r / min for 5-15 hours, cooled to room temperature, and evaporated to remove the solvent to obtain a binary copolymer; wherein the mass ratio of the intermediate product B, n-propanol, glycidyl methacrylate, and azobisisobutyronitrile is (12-15):(150-300):(1.4-2.8):(0.04-0.06);

[0021] In the above process, citric acid plays the role of a cross-linking agent. Citric acid contains multiple carboxyl groups that can undergo esterification reaction with the hydroxyl groups in 3-butene-1-ol and 3-perfluorohexylpropanol to obtain an intermediate product B containing a carbon-carbon double bond, a fluorinated hydrophobic chain, a hydroxyl group, and a carboxyl group; the intermediate product B is copolymerized with glycidyl methacrylate (containing a carbon-carbon double bond and an epoxy group) under the initiation of azobisisobutyronitrile to form a binary copolymer.

[0022] Preferably, in step (3), the method for preparing the modified polyurethane emulsion comprises the following steps:

[0023] Add polytetrahydrofuran to butanone, then add hydroxyl-terminated polydimethylsiloxane, stir for 20-30 minutes, add isophorone diisocyanate and dibutyltin dilaurate, heat to 60-80°C and stir for 1.5-2.5 hours, then add modified reduced graphene oxide, stir for 1.5-2.5 hours at 60-80°C, then add binary copolymer, continue to stir for 1.5-2.5 hours at 60-80°C, cool to room temperature, and distill to remove organic solvent to obtain modified polyurethane;

[0024] In the above process, polytetrahydrofuran, hydroxyl-terminated polydimethylsiloxane, and isophorone diisocyanate react to form a prepolymer, and then the modified reduced graphene oxide and the binary copolymer are introduced into the polyurethane chain through the reaction between the isocyanate and the hydroxyl group.

[0025] Furthermore, in step (3), the mass ratios of polytetrahydrofuran, butanone, hydroxy-terminated polydimethylsiloxane, isophorone diisocyanate, dibutyltin dilaurate, modified reduced graphene oxide, and binary copolymer are (7.5-18.8):(100-200):(10-15):(2.2-4.4):(0.05-0.08):(2.5-5):(3.4-5.1).

[0026] Preferably, in step (4), the content of each component in the high adhesion waterproof coating is, by weight, 30-50 parts of modified polyurethane, 30-50 parts of hybrid material, 100-150 parts of deionized water, 15-30 parts of BYK-024 defoamer, and 10-30 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate; the mixing temperature is 40-50°C, and the curing conditions are: pre-curing at 60-80°C for 10-12h, and then curing at 120-140°C for 3-5h.

[0027] Furthermore, in step (4), the method for preparing the hybrid material comprises the following steps:

[0028] Step S1, mixing 4-aminophenol, paraformaldehyde, dehydroabietylamine and dioxane, heating to 70-80°C and stirring for 20-40min, heating to 100-120°C and reacting for 10-16h. After the reaction is completed, cooling the crude product to room temperature, washing, distilling and recrystallizing to obtain an intermediate product C; wherein the mass ratio of 4-aminophenol, paraformaldehyde, dehydroabietylamine and dioxane is (2.3-4.6):(10-20):(4.7-9.4):(100-150);

[0029] In the above process, 4-aminophenol is used as a phenol source and dehydroabietylamine is used as an amine source to react to obtain an intermediate product C containing a benzoxazine structure;

[0030] Step S2, adding nano silicon carbide powder to ethanol, adding ammonia water and deionized water, ultrasonically treating for 20-40 minutes, stirring for 10-30 minutes, then adding tetraethyl silicate and hexadecyltrimethoxysilane, continuing to stir at room temperature for 20-30 hours, and finally adding acetic acid to the mixed solution, centrifuging and drying to obtain composite nanoparticles; wherein the mass ratio of nano silicon carbide powder, ethanol, ammonia water, deionized water, tetraethyl silicate, acetic acid and hexadecyltrimethoxysilane is (0.5-1):(200-300):(6-12):(6-12):(1-3):(6-12):(0.5-1.5);

[0031] 3-glycidyloxypropyltrimethoxysilane is added to an ethanol aqueous solution with a volume fraction of 90%, and the pH is adjusted to 3-4 by an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then composite nanoparticles are added, heated in a water bath at 60-70°C, and stirred at a speed of 400-600 r / min for 20-40 min, filtered, washed, and dried to obtain modified composite nanoparticles; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, ethanol aqueous solution, and composite nanoparticles is (0.05-0.15):(0.15-0.45):(0.5-1.5);

[0032] In the above process, tetraethyl silicate is hydrolyzed to silicon dioxide on the surface of silicon carbide, thereby in-situ growing silicon dioxide on the surface of silicon carbide, the addition of hexadecyltrimethoxysilane makes the surface of the composite nanoparticles more hydrophobic, and then 3-glycidyloxypropyltrimethoxysilane is used to introduce epoxy groups on the surface of the composite nanoparticles;

[0033] Add the modified composite nanoparticles to dimethylformamide, stir at a speed of 300-500 r / min for 20-40 min, then add the intermediate product C, stir at a speed of 200-400 r / min at 70-90° C. for 20-28 h, centrifuge, wash, and dry to obtain a hybrid material; wherein the mass ratio of the modified composite nanoparticles, dimethylformamide, and the intermediate product is (0.5-1):(20-40):(0.3-0.8);

[0034] In the above process, the epoxy group in the modified composite nanoparticles reacts with the amino group in the intermediate product C, and the modified composite nanoparticles and the intermediate product C are combined in the form of chemical bonds to form an organic-inorganic composite hybrid material.

[0035] The high-adhesion waterproof coating is prepared by the method for preparing the high-adhesion waterproof coating.

[0036] The high-adhesion waterproof coating is used on profiles, especially aluminum alloy door and window profiles.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The present invention uses modified reduced graphene oxide and a binary copolymer as modifiers to prepare a modified polyurethane emulsion. The polymerized long chains of the binary copolymer are cross-linked with the polyurethane chains and the multiple branches of the modified reduced graphene oxide to increase the cross-linking density of the polyurethane system, thereby improving the mechanical properties, wear resistance, waterproof properties and cohesion of the coating. The enhancement of the cohesion improves the adhesion between the coating and the aluminum alloy profile. The high aspect ratio and inherent barrier properties of the modified reduced graphene oxide improve the waterproof performance by increasing the diffusion path of water molecules. Its high specific surface area increases the interface area between the coating and the aluminum alloy profile, promoting the improvement of the adhesion of the coating. In addition, due to the lubricating properties of the reduced graphene oxide, the wear resistance of the coating can be enhanced. Through the intermediate product A introduces multiple side chains containing disulfide bonds, imine bonds, and phenolic hydroxyl groups into the grafted modified reduced graphene oxide, and then connects them to the polyurethane chain to improve the dispersibility of inorganic reduced graphene oxide; and the disulfide bonds and imine bonds in the intermediate product A are dynamic bonds, which cooperate with the hydrogen bonds in the polyurethane cross-linked network, and the joint action of multiple dynamic bonds gives the polyurethane emulsion excellent self-healing properties; further, the grafting of the binary copolymer introduces a large number of epoxy groups and fluorinated hydrophobic chains into the polyurethane system, and the epoxy groups cooperate with the phenolic hydroxyl groups in the modified reduced graphene oxide side chains to form a strong adsorption layer between the aluminum alloy profile, thereby forming a strong adhesion between the coating and the aluminum alloy profile, and the fluorinated hydrophobic chains have a positive effect on improving the waterproof performance of the coating.

[0039] The silicon carbide in the present invention has good hardness and can enhance the wear resistance of the coating as a filler in the coating. Silicon dioxide is grown in situ on the surface of silicon carbide to obtain hydrophobic composite nanoparticles, and then epoxy groups are introduced on the surface of the composite nanoparticles to react with an intermediate product C containing benzoxazine to obtain an organic-inorganic composite hybrid material. The inorganic composite nanoparticles are connected to the organic structure of the intermediate product C to improve the dispersibility of the composite nanoparticles, and the unreacted epoxy groups on the surface of the modified composite nanoparticles are helpful to improve the adhesion of the coating. Benzoxazine has good hydrophobic effect and mechanical properties, and then the hybrid material is mixed with modified polyurethane to form a semi-interpenetrating network structure between the hybrid material and the modified polyurethane, so as to further improve the mechanical properties, wear resistance, waterproof performance and adhesion of the coating system. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a process flow chart of a method for preparing a high-adhesion waterproof coating of the present invention;

[0041] Figure 2 It is a comparison chart of the wear rate test of the high adhesion waterproof coating of Examples 2-4 of the present invention and Comparative Examples 3-9;

[0042] Figure 3 This is a comparison diagram of water contact angle tests of high adhesion waterproof coatings of Examples 2-4 of the present invention and Comparative Examples 3-9;

[0043] Figure 4 It is a comparison chart of adhesion test of high adhesion waterproof coatings of Examples 2-4 of the present invention and Comparative Examples 3-9;

[0044] Figure 5 It is a schematic diagram of the synthesis of the intermediate product A of the present invention;

[0045] Figure 6 It is a schematic diagram of the synthesis of the intermediate product B of the present invention;

[0046] Figure 7 It is a schematic diagram of the synthesis of the intermediate product C of the present invention. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] Example 1: This example discloses a method for preparing a hybrid material, comprising the following steps:

[0049] Step S1, 3.5 g of 4-aminophenol, 15 g of paraformaldehyde, 7.1 g of dehydroabietylamine and 120 g of dioxane were mixed, heated to 75° C. and stirred for 30 min, then heated to 110° C. for reaction for 12 h. After the reaction was completed, the crude product was cooled to room temperature and washed 4 times with 1 wt % sodium bicarbonate aqueous solution and deionized water respectively to remove all traces of unreacted phenolic products, and water and toluene were removed by vacuum distillation at 70° C., and then recrystallized with ethanol to obtain an intermediate product C;

[0050] Step S2, adding 0.8 g of nano silicon carbide powder to 250 g of ethanol, adding 9 g of ammonia water and 9 g of deionized water, ultrasonically treating for 30 min, then stirring for 20 min, then adding 2 g of tetraethyl silicate and 1 g of hexadecyltrimethoxysilane and continuing to stir at room temperature for 25 h, finally adding 9 g of acetic acid to the mixed solution, centrifuging and drying to obtain composite nanoparticles;

[0051] 0.1 g of 3-glycidyloxypropyltrimethoxysilane was added to 0.3 g of 90% ethanol aqueous solution, the pH was adjusted to 3.5 by 0.1 mol / L acetic acid aqueous solution, 1 g of composite nanoparticles was added, heated in a water bath at 65° C., stirred at 500 r / min for 30 min, filtered, washed, and dried to obtain modified composite nanoparticles;

[0052] 0.8 g of the modified composite nanoparticles were added to 30 g of dimethylformamide, stirred at 400 r / min for 30 min, and then 0.6 g of the intermediate product C was added, stirred at 80° C. at 300 r / min for 24 h, centrifuged, washed, and dried to obtain a hybrid material.

[0053] Embodiment 2: This embodiment discloses a method for preparing a high-adhesion waterproof coating, comprising the following steps:

[0054] Step (1), adding 15.4 g of 3,4,5-trihydroxybenzaldehyde to 50 g of ethanol, stirring until dissolved, then adding 10 g of 4,4'-dithiodiphenylamine, reflux reaction at 70° C. for 15 h, evaporating and removing the solvent to obtain a primary product, adding the primary product to 55 g of ethyl acetate, stirring for 20 min, centrifuging at a speed of 5000 r / min for 10 min, repeating the above washing and centrifugation operation twice, and finally drying the solid after centrifugation at 60° C. for 20 h to obtain an intermediate product A;

[0055] Step (2), dispersing 1 g of reduced graphene oxide in 400 g of N,N-dimethylformamide, ultrasonically treating for 1 h, then adding 10 g of hexamethylene diisocyanate isocyanurate trimer, reacting at 70° C. for 30 h in a nitrogen atmosphere, then adding 10.5 g of intermediate product A, keeping the temperature constant, and continuing to react for 2 h. After the reaction is completed, centrifuging, washing the obtained centrifuged product with N,N-dimethylformamide 4 times, and drying to obtain modified reduced graphene oxide;

[0056] Step (3), adding 1 g of 3-butene-1-ol and 3.8 g of 3-perfluorohexylpropanol to 100 g of dimethyl sulfoxide, and then adding 2.5 g of citric acid and 0.06 g of sodium hypophosphite, heating to 70° C., stirring at a speed of 200 r / min for 2.5 h, after the reaction is completed, removing the solvent by reduced pressure distillation at 55° C., and then dialyzing through a dialysis bag with a molecular weight cutoff of 200D to obtain an intermediate product B;

[0057] 12 g of intermediate product B was added to 150 g of n-propanol, and ultrasonically mixed for 20 min. Then, 1.4 g of glycidyl methacrylate and 0.04 g of azobisisobutyronitrile were added. The mixture was heated to 50° C. in a nitrogen atmosphere, stirred at a speed of 200 r / min for 15 h, cooled to room temperature, and the solvent was evaporated to obtain a binary copolymer.

[0058] 7.5 g of polytetrahydrofuran was added to 100 g of butanone, and then 10 g of hydroxyl-terminated polydimethylsiloxane was added, and the mixture was stirred for 20 min. 2.2 g of isophorone diisocyanate and 0.05 g of dibutyltin dilaurate were added, and the mixture was heated to 60° C. and stirred for reaction for 2.5 h. 2.5 g of modified reduced graphene oxide was added, and the mixture was stirred for reaction at 60° C. for 2.5 h. Then 3.4 g of the binary copolymer was added, and the mixture was stirred for reaction at 60° C. for 2.5 h. The mixture was cooled to room temperature, and the organic solvent was removed by distillation to obtain a modified polyurethane.

[0059] Step (4), by weight, 30 parts of modified polyurethane, 30 parts of hybrid material, 100 parts of deionized water, 15 parts of BYK-024 defoamer, and 10 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate are mixed evenly at 40°C, pre-cured at 60°C for 12 hours, and then cured at 120°C for 5 hours to obtain a high-adhesion waterproof coating.

[0060] Embodiment 3: This embodiment discloses a method for preparing a high-adhesion waterproof coating, comprising the following steps:

[0061] Step (1), adding 30.8 g of 3,4,5-trihydroxybenzaldehyde to 100 g of ethanol, stirring until dissolved, then adding 20 g of 4,4'-dithiodiphenylamine, reflux reaction at 90° C. for 10 h, evaporating to remove the solvent, obtaining a primary product, adding the primary product to 110 g of ethyl acetate, stirring for 40 min, centrifuging at 7000 r / min for 5 min, repeating the above washing and centrifugation operation 4 times, and finally drying the solid after centrifugation at 80° C. for 10 h to obtain an intermediate product A;

[0062] Step (2), dispersing 2 g of reduced graphene oxide in 800 g of N,N-dimethylformamide, ultrasonically treating for 1.5 h, then adding 18 g of hexamethylene diisocyanate isocyanurate trimer, reacting at 90° C. for 20 h in a nitrogen atmosphere, then adding 18.8 g of intermediate product A, keeping the temperature constant, and continuing to react for 4 h. After the reaction is completed, centrifuging, washing the obtained centrifuged product with N,N-dimethylformamide 8 times, and drying to obtain modified reduced graphene oxide;

[0063] Step (3), adding 2 g of 3-butene-1-ol and 7.6 g of 3-perfluorohexylpropanol to 300 g of dimethyl sulfoxide, and then adding 5 g of citric acid and 0.1 g of sodium hypophosphite, heating to 90° C., stirring at a speed of 400 r / min for 1.5 h, after the reaction is completed, removing the solvent by reduced pressure distillation at 65° C., and then dialyzing through a dialysis bag with a molecular weight cutoff of 200D to obtain an intermediate product B;

[0064] 15 g of intermediate product B was added to 300 g of n-propanol, and ultrasonically mixed for 40 min. Then, 2.8 g of glycidyl methacrylate and 0.06 g of azobisisobutyronitrile were added. The mixture was heated to 70° C. in a nitrogen atmosphere, and stirred at a speed of 400 r / min for 5 h. The mixture was cooled to room temperature, and the solvent was evaporated to obtain a binary copolymer.

[0065] 18.8 g of polytetrahydrofuran was added to 200 g of butanone, and then 15 g of hydroxyl-terminated polydimethylsiloxane was added, and the mixture was stirred for 30 min. 4.4 g of isophorone diisocyanate and 0.08 g of dibutyltin dilaurate were added, and the mixture was heated to 80° C. and stirred for 1.5 h. 5 g of modified reduced graphene oxide was added, and the mixture was stirred for 1.5 h at 80° C., and then 5.1 g of the binary copolymer was added, and the mixture was stirred for 1.5 h at 80° C., and the mixture was cooled to room temperature, and the organic solvent was removed by distillation to obtain a modified polyurethane.

[0066] Step (4), by weight, 50 parts of modified polyurethane, 50 parts of hybrid material, 150 parts of deionized water, 30 parts of BYK-024 defoamer, and 30 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate are mixed evenly at 50° C., pre-cured at 80° C. for 10 hours, and then cured at 140° C. for 3 hours to obtain a high-adhesion waterproof coating.

[0067] Embodiment 4: This embodiment discloses a method for preparing a high-adhesion waterproof coating, comprising the following steps:

[0068] Step (1), adding 23.1 g of 3,4,5-trihydroxybenzaldehyde to 75 g of ethanol, stirring until dissolved, then adding 15 g of 4,4'-dithiodiphenylamine, reflux reaction at 80°C for 12 h, evaporating and removing the solvent to obtain a primary product, adding the primary product to 82.5 g of ethyl acetate, stirring for 30 min, centrifuging at 6000 r / min for 8 min, repeating the above washing and centrifugation operation 3 times, and finally drying the solid after centrifugation at 70°C for 15 h to obtain an intermediate product A;

[0069] Step (2), dispersing 1.5 g of reduced graphene oxide in 600 g of N,N-dimethylformamide, ultrasonically treating for 1.2 h, then adding 14 g of hexamethylene diisocyanate isocyanurate trimer, reacting at 80° C. for 25 h in a nitrogen atmosphere, then adding 14.7 g of intermediate product A, keeping the temperature constant, and continuing the reaction for 3 h. After the reaction is completed, centrifuging, washing the obtained centrifuged product with N,N-dimethylformamide for 6 times, and drying to obtain modified reduced graphene oxide;

[0070] Step (3), adding 1.5 g of 3-butene-1-ol and 5.7 g of 3-perfluorohexylpropanol to 200 g of dimethyl sulfoxide, and then adding 3.8 g of citric acid and 0.08 g of sodium hypophosphite, heating to 80° C., stirring at a speed of 300 r / min for 2 h, after the reaction is completed, removing the solvent by reduced pressure distillation at 60° C., and then dialyzing through a dialysis bag with a molecular weight cutoff of 200D to obtain an intermediate product B;

[0071] 13.5 g of intermediate product B was added to 250 g of n-propanol, and ultrasonically mixed for 30 min. Then, 2.1 g of glycidyl methacrylate and 0.05 g of azobisisobutyronitrile were added. The mixture was heated to 60° C. in a nitrogen atmosphere, stirred at a speed of 300 r / min for 10 h, cooled to room temperature, and the solvent was evaporated to obtain a binary copolymer.

[0072] 13.2 g of polytetrahydrofuran was added to 150 g of butanone, and then 12.5 g of hydroxyl-terminated polydimethylsiloxane was added, and the mixture was stirred for 25 min. 3.3 g of isophorone diisocyanate and 0.06 g of dibutyltin dilaurate were added, and the mixture was heated to 70° C. and stirred for reaction for 2 h. 3.8 g of modified reduced graphene oxide was added, and the mixture was stirred for reaction at 70° C. for 2 h. Then 4.2 g of the binary copolymer was added, and the mixture was stirred for reaction at 70° C. for 2 h. The mixture was cooled to room temperature, and the organic solvent was removed by distillation to obtain a modified polyurethane.

[0073] Step (4), by weight, 40 parts of modified polyurethane, 40 parts of hybrid material, 120 parts of deionized water, 25 parts of BYK-024 defoamer, and 20 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate are mixed evenly at 45°C, pre-cured at 70°C for 11 hours, and then cured at 130°C for 4 hours to obtain a high-adhesion waterproof coating.

[0074] The hybrid materials in the above Examples 2-4 adopt the hybrid material prepared in Example 1.

[0075] Comparative Example 1

[0076] Comparative Example 1 Compared with Example 1, in the process of preparing the hybrid material in Comparative Example 1, nano-silicon carbide is used instead of the composite nanoparticles, that is, silicon dioxide is not grown on the surface of silicon carbide, and other conditions remain unchanged.

[0077] Comparative Example 2

[0078] Comparative Example 2 Compared with Example 1, in the process of preparing the hybrid material in Comparative Example 2, composite nanoparticles are used instead of modified composite nanoparticles, and other conditions remain unchanged.

[0079] Comparative Example 3

[0080] Comparative Example 3 Compared with Example 4, Comparative Example 3 uses the hybrid material prepared in Comparative Example 1, and other conditions remain unchanged.

[0081] Comparative Example 4

[0082] Comparative Example 4 Compared with Example 4, Comparative Example 4 uses the hybrid material prepared in Comparative Example 2, and other conditions remain unchanged.

[0083] Comparative Example 5

[0084] Comparative Example 5 Compared with Example 4, the high adhesion waterproof coating of Comparative Example 5 uses modified composite nanoparticles instead of hybrid materials, and other conditions remain unchanged.

[0085] Comparative Example 6

[0086] Comparative Example 6 Compared with Example 4, in Comparative Example 6, no intermediate product A was added during the preparation of modified reduced graphene oxide, and other conditions remained unchanged.

[0087] Comparative Example 7

[0088] Comparative Example 7 Compared with Example 4, in Comparative Example 7, no binary copolymer was added during the preparation of the modified polyurethane, and other conditions remained unchanged.

[0089] Comparative Example 8

[0090] Compared with Example 4, in Comparative Example 8, the intermediate product A is used instead of the modified reduced graphene oxide during the preparation of the modified polyurethane, and other conditions remain unchanged.

[0091] Comparative Example 9

[0092] Compared with Example 4, in Comparative Example 9, no hybrid material was added during the preparation of the high-adhesion waterproof coating, and other conditions remained unchanged.

[0093] In the above embodiments and comparative examples, reduced graphene oxide, product number CRG001, thickness of about 1nm, single layer diameter of 05-9.98μm, carbon content of about 83.35wt%, oxygen content of about 7.58wt%, from Chihe New Materials Technology Nanjing Co., Ltd.; hexamethylene diisocyanate isocyanurate trimer, CAS No. 3779-63-3, molecular weight 504.58, melting point>300℃, boiling point 648.2±50.0℃, density 1.20±0.1g / cm3, from Wuhan Vogda Biotechnology Co., Ltd.; dialysis bag, product name dry dialysis bag 10-200D, molecular weight cutoff 200D, flattened width 10mm, diameter 6mm, from Zhejiang Lianshuo Biotechnology Co., Ltd.; polytetrahydrofuran, molecular weight Mn=2000g / mol, density 0.9±0.0g / cm 3 , flash point is 58.1℃, boiling point is 195.7℃, from Wuhan Jushun Chemical Co., Ltd.; BYK-024 defoamer, the main ingredient is silicone, the active ingredient content is 96%, appearance: liquid, density is 1.01kg / m³, from Dongguan Haoyouduo New Materials Co., Ltd.; hydroxyl-terminated polydimethylsiloxane, viscosity is 45-85cSt, brand is Gelest, from Shanghai Mairui Biochemical Technology Co., Ltd.; nano silicon carbide powder, particle size is 30nm, shape is spherical, item number XT-SiC, from Shanghai Xiangtian Nanomaterials Co., Ltd.; polyformaldehyde, melting point 175℃, density 1.42g / mL, vapor density 1.03 (vs air), brand is Aladdin, from Guangzhou Xinhong Trading Co., Ltd.

[0094] Experimental example

[0095] A 2024T3 aluminum plate was selected as a substrate, and the high-adhesion waterproof coatings of Examples 2-4 and Comparative Examples 3-9 were coated on the AA2024-T3 substrate, respectively, with a dry coating thickness of 10 μm. The performance of the coated aluminum plate was tested.

[0096] 1. Water contact angle test: Tested by KRUSS DSA100 contact angle meter.

[0097] 2. Wear resistance test: Use a surface profiler to measure the wear amount, and then calculate the wear rate to characterize the wear resistance of the coating. The wear rate is calculated using the following formula:

[0098]

[0099] Where ΔV is the wear volume change, mm 3 ; S is the stroke, m; P is the load size, N.

[0100] 3. Adhesion test: It is carried out according to GB / T 5210-2006 "Adhesion test of paint and varnish by pull-off method".

[0101] The test results are shown in Table 1:

[0102]

[0103] It can be seen from the test results in Table 1 that the high-adhesion waterproof coatings prepared in Examples 2-4 of the present invention have excellent waterproofness and wear resistance, and have strong adhesion to aluminum alloy substrates. From the comparison between Comparative Example 3 and Example 4, it can be seen that by in-situ growing silicon dioxide on the surface of silicon carbide, hydrophobic composite nanoparticles can be obtained, which helps to improve the waterproof performance of the coating; from the comparison between Comparative Example 4 and Example 4, it can be seen that the introduction of epoxy groups on the surface of composite nanoparticles can enable the composite nanoparticles to be connected to the organic structure of intermediate product C, improve the dispersibility of composite nanoparticles, and modify the unreacted epoxy groups on the surface of composite nanoparticles to help improve the adhesion of the coating; from the comparison between Comparative Example 5 and Example 4, it can be seen that intermediate product C in the hybrid material introduces a benzoxazine structure to form a semi-interpenetrating network structure between the hybrid material and the modified polyurethane, further improving the mechanical properties, wear resistance, waterproof performance and adhesion of the coating system; from the comparison between Comparative Example 6 and Example 4, it can be seen that intermediate product A improves the coating by introducing phenolic hydroxyl groups in the modified polyurethane. The adhesion of the polyurethane is improved, and the grafting modification of the intermediate product A to the polyurethane is helpful to improve the crosslinking density of the polyurethane system, thereby improving various performances of the coating; from the comparison of comparative example 7 with example 4, it can be seen that by introducing the binary copolymer into the modified polyurethane, on the one hand, the crosslinking density of the polyurethane system is improved, and on the other hand, the epoxy group and the hydrophobic fluorine-containing chain are introduced, thereby improving the wear resistance, water resistance and adhesion of the coating; from the comparison of comparative example 8 with example 4, it can be seen that due to the inherent barrier and lubricity of reduced graphene oxide, it is helpful to improve the wear resistance and hydrophobicity of the coating. In addition, its high specific surface area increases the interface area between the coating and the aluminum alloy profile, and promotes the improvement of the adhesion of the coating; from the comparison of comparative example 9 with example 4, it can be seen that the modified composite nanoparticles in the hybrid material synergistically act with the intermediate product C, which has a significant effect on the improvement of various performances of the coating.

[0104] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-adhesion waterproof coating, characterized in that: The following steps are involved: Step (1), 3,4,5-trihydroxybenzaldehyde reacts with 4,4'-dithiodiphenylamine to obtain an intermediate product A; The preparation method of intermediate product A specifically comprises the following steps: Add 3,4,5-trihydroxybenzaldehyde to ethanol, stir until dissolved, then add 4,4'-dithiodiphenylamine, reflux at 70-90°C for 10-15h, evaporate to remove the solvent, obtain a primary product, add ethyl acetate to wash, stir for 20-40min, centrifuge, repeat the above washing and centrifugation operation 2-4 times, and dry to obtain an intermediate product A; Wherein, the mass ratio of 3,4,5-trihydroxybenzaldehyde, 4,4'-dithiodiphenylamine, ethanol and ethyl acetate is (15.4-30.8):(10-20):(50-100):(55-110); Step (2), modifying the reduced graphene oxide with the intermediate product A to obtain modified reduced graphene oxide; The preparation method of modified reduced graphene oxide specifically comprises the following steps: Dispersing reduced graphene oxide in N,N-dimethylformamide, ultrasonically treating for 1-1.5 hours, adding hexamethylene diisocyanate isocyanurate trimer, reacting at 70-90° C. for 20-30 hours in a nitrogen atmosphere, adding intermediate product A, keeping the temperature constant, and continuing to react for 2-4 hours. After the reaction is completed, centrifuging, washing, and drying to obtain modified reduced graphene oxide; Wherein, the mass ratio of reduced graphene oxide, N,N-dimethylformamide, hexamethylene diisocyanate isocyanurate trimer, and intermediate product A is (1-2): (400-800): (10-18): (10.5-18.8); Step (3), using citric acid as a crosslinking agent, reacting 3-butene-1-ol with 3-perfluorohexylpropanol to obtain an intermediate product B; copolymerizing the intermediate product B with glycidyl methacrylate to obtain a binary copolymer; The method for preparing the binary copolymer specifically comprises the following steps: 3-Butene-1-ol and 3-perfluorohexylpropanol are added to dimethyl sulfoxide, and then citric acid and sodium hypophosphite are added, and the mixture is heated to 70-90°C, and stirred at a speed of 200-400 r / min for 1.5-2.5 hours. After the reaction is completed, the solvent is removed by reduced pressure distillation at 55-65°C, and then dialyzed through a dialysis bag with a molecular weight cutoff of 200D to obtain an intermediate product B; Wherein, the mass ratio of 3-butene-1-ol, 3-perfluorohexylpropanol, dimethyl sulfoxide, citric acid and sodium hypophosphite is (1-2):(3.8-7.6):(100-300):(2.5-5):(0.06-0.1); The intermediate product B is added to n-propanol, and ultrasonically mixed for 20-40 minutes, and then glycidyl methacrylate and azobisisobutyronitrile are added, and the mixture is heated to 50-70° C. in a nitrogen atmosphere, and stirred at a speed of 200-400 r / min for 5-15 hours, and then cooled to room temperature, and the solvent is evaporated to obtain a binary copolymer; Wherein, the mass ratio of the intermediate product B, n-propanol, glycidyl methacrylate, and azobisisobutyronitrile is (12-15):(150-300):(1.4-2.8):(0.04-0.06); Using binary copolymer and modified reduced graphene oxide as modifiers, modified polyurethane is prepared; The preparation method of the modified polyurethane emulsion specifically comprises the following steps: Add polytetrahydrofuran to butanone, then add hydroxyl-terminated polydimethylsiloxane, stir for 20-30 minutes, add isophorone diisocyanate and dibutyltin dilaurate, heat to 60-80°C and stir for 1.5-2.5 hours, then add modified reduced graphene oxide, stir for 1.5-2.5 hours at 60-80°C, then add binary copolymer, continue to stir for 1.5-2.5 hours at 60-80°C, cool to room temperature, and distill to remove organic solvent to obtain modified polyurethane; The mass ratios of the polytetrahydrofuran, butanone, hydroxy-terminated polydimethylsiloxane, isophorone diisocyanate, dibutyltin dilaurate, modified reduced graphene oxide, and binary copolymer are (7.5-18.8):(100-200):(10-15):(2.2-4.4):(0.05-0.08):(2.5-5):(3.4-5.1); Step (4), mixing the modified polyurethane, the hybrid material, deionized water, BYK-024 defoamer, and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and curing to obtain a high-adhesion waterproof coating; Wherein, the hybrid material is prepared by the following steps: Step S1, reacting 4-aminophenol, paraformaldehyde and dehydroabietylamine to obtain an intermediate product C; Step S2, in situ growing nano-silicon dioxide on the surface of nano-silicon carbide to obtain composite nano-particles, and then modifying them with 3-glycidyloxypropyltrimethoxysilane to obtain modified composite nano-particles; The modified composite nanoparticles react with the intermediate product C to obtain a hybrid material.

2. The method for preparing a high-adhesion waterproof coating according to claim 1, characterized in that: In the step (4), the content of each component in the high adhesion waterproof coating is, by weight, 30-50 parts of modified polyurethane, 30-50 parts of hybrid material, 100-150 parts of deionized water, 15-30 parts of BYK-024 defoamer, and 10-30 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate; the mixing temperature is 40-50°C, and the curing conditions are: pre-curing at 60-80°C for 10-12h, and then curing at 120-140°C for 3-5h.

3. The method for preparing a high-adhesion waterproof coating according to claim 1, characterized in that: In step (4), the method for preparing the hybrid material specifically comprises the following steps: Step S1, mixing 4-aminophenol, paraformaldehyde, dehydroabietylamine and dioxane, heating to 70-80°C and stirring for 20-40min, heating to 100-120°C and reacting for 10-16h. After the reaction is completed, cooling the crude product to room temperature, washing, distilling and recrystallizing to obtain an intermediate product C; wherein the mass ratio of 4-aminophenol, paraformaldehyde, dehydroabietylamine and dioxane is (2.3-4.6):(10-20):(4.7-9.4):(100-150); Step S2, adding nano silicon carbide powder to ethanol, adding ammonia water and deionized water, ultrasonically treating for 20-40 minutes, stirring for 10-30 minutes, then adding tetraethyl silicate and hexadecyltrimethoxysilane, continuing to stir at room temperature for 20-30 hours, and finally adding acetic acid to the mixed solution, centrifuging and drying to obtain composite nanoparticles; wherein the mass ratio of nano silicon carbide powder, ethanol, ammonia water, deionized water, tetraethyl silicate, acetic acid and hexadecyltrimethoxysilane is (0.5-1):(200-300):(6-12):(6-12):(1-3):(6-12):(0.5-1.5); 3-glycidyloxypropyltrimethoxysilane is added to an ethanol aqueous solution with a volume fraction of 90%, and the pH is adjusted to 3-4 by an acetic acid aqueous solution with a concentration of 0.1 mol / L, and then composite nanoparticles are added, heated in a water bath at 60-70°C, and stirred at a speed of 400-600 r / min for 20-40 min, filtered, washed, and dried to obtain modified composite nanoparticles; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, ethanol aqueous solution, and composite nanoparticles is (0.05-0.15):(0.15-0.45):(0.5-1.5); Step S3, adding the modified composite nanoparticles to dimethylformamide, stirring at a speed of 300-500 r / min for 20-40 min, then adding the intermediate product C, stirring at a speed of 200-400 r / min at 70-90°C for 20-28 h, centrifuging, washing, and drying to obtain a hybrid material; wherein the mass ratio of the modified composite nanoparticles, dimethylformamide, and the intermediate product is (0.5-1):(20-40):(0.3-0.8).

4. A high-adhesion waterproof coating prepared by the preparation method of the high-adhesion waterproof coating as described in any one of claims 1 to 3.

5. Application of the high adhesion waterproof coating as claimed in claim 4 on profiles.

Citation Information

Patent Citations

  • Waterproof aluminium alloy material and applications thereof

    CN110499075A

  • Preparation method of graphene-modified polyurethane conductive coating

    CN104804169A

  • Martensitic stainless steel surface hardening agent as well as preparation method and application method thereof

    CN111593296A